Sustained circulation of enterovirus D68 in Europe in 2023 and the continued evolution of enterovirus D68 B3-lineages associated with distinct amino acid substitutions in VP1 protein - Hirvonen, Aurora (Elsevier BV, 2025)
Background
Enterovirus D68 (EV-D68) causes respiratory disease ranging from mild to severe and in rare cases a paralytic syndrome, called acute flaccid myelitis (AFM). Since the global EV-D68 outbreak in 2014, the virus has mainly circulated in biennial epidemic cycles with peaks detected during even years. However, following the COVID-19 pandemic, the seasonal pattern of EV-D68 has been characterized by large yearly upsurges. Here, we describe the circulation of EV-D68 in Europe in 2023 and track its genetic evolution.
Study design
Data was compiled from members of the European Non-Polio Network (ENPEN). This included monthly data on the total number of EV samples tested, EV positive samples, EV-D68 positive samples and cases, and other EV positive samples detected in 2023. Information on sample types and surveillance system was recorded. Sequence data from the VP1 gene was used for phylogenetic and amino acid sequence analysis.
Results
EV was detected in 13,585 out of 203,622 diagnostic samples tested (6.7 %), of which 402 (3.0 %) were determined as EV-D68, representing 386 cases. EV-D68 infections peaked in October 2023 (136/386; 35.2 %). 267/386 (69.2 %) of EV-D68 cases were captured through clinical EV surveillance, almost all of which (202/204 of positive samples with sample type information) were detected in respiratory specimens. Phylogenetic analysis performed on 99 VP1 sequences revealed a distinct B3-derived lineage with a previously undescribed residue change, D554E, in Europe.
Conclusions
​​​​​​​The study documents sustained circulation of EV-D68 in Europe in 2023, the evolution of B3-derived lineages, and appearance of previously undescribed amino acid substitutions in Europe. This stresses the need for continuous EV-D68 surveillance and harmonization of EV-D68 detection practices towards better data comparability across countries.